Testimony on Trial : Conrad, James, and the Contest for Modernism - Artese, Brian, 1969- (Book collections on Project MUSE., 2012)
Testimony on Trial examines the conflicts over testimony through the eyes of two of its major combatants, Joseph Conrad and Henry James. Brian Artese finds an overlooked yet direct inspiration for Heart of Darkness in the anti-testimonial scheming of Henry Morton Stanley and the New York Herald. Through new readings of works including Lord Jim and The Portrait of a Lady, Artese demonstrates how the cultural conditions that worked against testimony fed into a nascent conflict about the meaning of modernism itself."--Pub. desc.